Cryptosporidiosis: a neglected infection and its association with nutritional status in schoolchildren in northwestern Mexico - Quihui-Cota, Luis; Lugo-Flores, Carmen M; Ponce-Martínez, Jose A; Morales-Figueroa, Gloria G (The Journal of Infection in Developing Countries, 2015)
Introduction: Undernutrition is a recognized public health problem in Mexican children and cryptosporidiosis is probably a factor contributing to this problem. However, it remains a neglected and poorly attended infection in Mexico. This study aimed to determine the prevalence of Cryptosporidium parvum and to establish its association with the nutritional status in schoolchildren of northwestern Mexico. Methodology: A total of 405 schoolchildren between 6 and 13 years of age were included in this study. Weight-for-age (W/A), height-for-age (H/A) and body mass index-for-age (BMI/A) Z scores were calculated. The Faust technique was used to detect intestinal parasites in stool samples and C. parvum coproantigen was detected by enzyme-linked immunosorbent assay (ELISA). Results: The overall prevalence of C. parvum was 28.4%. Some of the study children were C. parvum free (n = 86) and some were C. parvum infected (n = 77). The prevalences of risk of undernutrition found in both groups of children for H/A, W/A, and BMI/A Z scores were 18%, 21% and 28%, respectively. Weight, ZW/A, and ZH/A were significantly higher in the C. parvum-free group compared to the C. parvum-infected group (p ≤ 0.05). The children with cryptosporidiosis were 2.7 times more likely to be at risk of undernutrition by W/A Z score and 2.9 times more likely to be at risk of undernutrition by ZH/A than were the C. parvum-free children. Conclusions: Cryptosporidiosis may be a contributing factor to childhood undernutrition in northwestern Mexico. The proper authorities must implement control and prevention measurements in Mexico and other developing countries.